Pengembangan Jiwa Kewirausahaan Pada Karang Taruna Kelurahan Cirendeu - Angga Pratama; Veta Lidya Delimah; Raden Roro Ayu Metarini (Universitas Pamulang, 2022)
The implementation of Community Service (PKM) is one of the applications of the Tri Dharma of Higher Education which in its implementation makes a positive contribution to the community. The implementation of this PKM takes the title